Digitalisasi Produk Bank Konvensional Dan Bank Syariah Di Indonesia - Andrew Shandy Utama (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2021)
Technological developments make the world borderless. The development of information and communication technology has touched the banking sector. Based on the operational system, the types of banks can be divided into conventional banks and Islamic banks. This study aims to explain the digitalization of conventional bank products and Islamic banks in Indonesia. The method used in this research is normative legal research. The development of information and communication technology has touched the banking sector. As one of the efforts to increase bank capability, more optimal utilization of information technology development is a prerequisite in supporting bank service innovation. Therefore, digital banking is a very potential business opportunity and an inevitable necessity in the banking sector in the digital era. In addition to increasing the efficiency of bank operational activities, digital banking can improve the service quality of conventional banks and Islamic banks to customers in transactions. The Financial Services Authority of the Republic of Indonesia then issued Financial Services Authority Regulation Number 12/POJK.03/2018 concerning the Implementation of Digital Banking Services by Commercial Banks. There are forms of e-Banking services that can be used at conventional banks and Islamic banks, namely ATM (Automated Teller Machine), EDC (Electronic Data Capture), internet banking, SMS banking, mobile banking, e-Commerce, phone banking, and video.